Utilizing Foundation Models and Reinforcement Learning for Intelligent Robotics: Enhancing Autonomous Task Performance in Dynamic Environments (Journal of Artificial Intelligence & Research, 2022)
The burgeoning field of intelligent robotics demands the development of agile and versatile agents that can effectively navigate and operate within dynamic and complex environments. This paper delves into the synergistic integration of foundation models (FMs) and reinforcement learning (RL) to achieve superior autonomous task performance for robots. FMs, pre-trained on massive datasets encompassing diverse modalities, exhibit exceptional capabilities in areas such as perception, language understanding, and world modeling. By capitalizing on these strengths, we explore how FMs can be leveraged to augment the decision-making processes employed within RL frameworks. This research posits that the amalgamation of FMs and RL can empower robots with several key advantages:Enhanced Situational Awareness: FMs facilitate the fusion of visual and language cues, leading to a more comprehensive understanding of the robot's surroundings. This enriched perception enables robots to make informed decisions and react more effectively to dynamic changes in the environment.Improved Task Planning: By incorporating commonsense reasoning gleaned from FMs, robots can achieve superior task planning capabilities. FMs encode a vast amount of world knowledge, allowing robots to reason about cause-and-effect relationships, object affordances, and environmental constraints. This knowledge informs the selection of appropriate actions and facilitates the formulation of more robust plans.Efficient Adaptation to Unforeseen Circumstances: RL's core strength lies in its ability to learn through trial and error, enabling robots to adapt their behaviors in response to unforeseen situations. The integration of FMs with RL can potentially enhance this capability. By providing robots with a richer understanding of the environment and the task at hand, FMs can guide exploration strategies within the RL framework, leading to faster convergence on optimal policies for novel scenarios.This paper presents a comprehensive review of the cutting-edge advancements in the integration of FMs and RL for intelligent robotics. We then delve into the theoretical underpinnings of this combined approach, outlining the potential benefits and challenges associated with its implementation. Finally, we discuss promising future research directions that capitalize on the burgeoning potential of FMs and RL to achieve unprecedented levels of autonomous robot performance in dynamic environments.